Current Status of Grevy Zebra: A Review - Kula Jilo; Nejash Abdela; Ahmed Mohammed (International Journal of Veterinary Science and Research - Peertechz Publications, 2016)
Grevy's zebra is a member of the horse family Equidae and so is closely related to horses, asses and other zebras. They inhabit dry desert regions and open grasslands. Grevy's zebra is one of the world's most threatened wild equids and is IUCN red-listed as endangered. Historically, the Grevy's zebra Equus grevyi ranged from east of the Rift Valley in Kenya to western Somalia and northern Ethiopia. Nowadays, Grevy's zebra is found only in Kenya and small isolated populations in Yabello Sanctuary Park in Ethiopia. They are regionally extinct in Djibouti, Eritrea and Somalia The number of Equus grevyi has declined rapidly by 85% over the last 27 years in the late 1970s the number estimates to be 15,000 but the current estimation is between 1,700 and 2,100. The species of grevy zebra are on the verge of extniction due to habitat degradation and loss, competition for resources with livestock, hunting, drought, disease, hybridisation and predation. Therefore, routine conservation strategies should be implemented as soon as possible..